The Role of Perceived Value and Social Influence in Roblox Avatar Clothing Purchase Decisions Among Generation Z Roblox Players in Cirebon City - Pipit Pitria; Muhammad Santoso; Keke Shabrina Nurmalitasari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
In the metaverse era, Roblox allows Gen Z to express their identity through virtual avatar clothing, with perceived value and social influence as the main drivers of purchase, although local research is still minimal. This study aims to examine the influence of both variables partially and simultaneously on the purchasing decisions of Roblox avatar clothing among Gen Z in Cirebon City. This type of quantitative, explanatory, causal research uses a 5-point Likert questionnaire on the Gen Z population (13-28 years old) active Roblox users who have purchased avatars; a sample of 201 respondents via purposive sampling (Lemeshow-Cochran formula). The instrument was validated (Pearson r>0.30) and reliable (Cronbach's α>0.70); analysis via SPSS includes descriptive, classical tests, and multiple linear regression. The results show that perceived value has a significant positive effect (β=0.719, t=13.667, p=0.000) and dominant, social influence is also significant (β=0.079, t=1.974, p=0.050); Simultaneous F=129.834 (p=0.000), R²=0.567. Conclusion: Both variables drive purchasing decisions, with perceived value being the most influential; implications for Roblox's marketing strategy.